Geographic variation in Trumpeter Swan Cygnus buccinator clutch size and egg weights - Olsen, Dave; Long, Bill; Mitchell, Carl D. (Wildfowl, 2015)
Because larger clutch sizes and heavier eggs may indicate fitness as well as resourceÂ availability, we investigated whether there were significant differences in clutch sizeÂ and egg weights between the Interior Population (IP) and Rocky MountainÂ Population (RMP) of Trumpeter Swans Cygnus buccinator in North America. A total ofÂ 1,113 eggs were measured or weighed at 283 nests. Average clutch size ranged fromÂ 3.5â€“5.8 eggs across study sites, and average egg mass ranged from 333.25â€“373.80 g.Â Average clutch size was significantly larger for IP swans (5.8 eggs per clutch) than forÂ those from the RMP (mean clutch size = 4.3 eggs). Egg weights were alsoÂ significantly heavier in the IP (mean = 366.43 g) than in the RMP (mean = 336.98 g).Â Mean clutch sizes and egg weights were within the range of other studies involvingÂ Trumpeter Swans. The results may provide some indication why the IP is increasingÂ at a faster rate than the RMP of Trumpeter Swans.